PENGARUH COMMUNICATION TRAINING DAN FREQUENT OF INTERNAL MEETING TERHADAP JOB SATISFACTION PADA PERAWAT RUMAH SAKIT UMUM SULTAN ISKANDAR MUDA NAGAN RAYA DENGAN INTERNAL COMMUNICATION SEBAGAI VARIABEL PEMEDIASI - Aja Bangsawan; Murkhana; Nurlina (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The study was conducted internally. The population in this study included all 305 nurses. Of these, 173 were selected as respondents. The sampling method used was probability sampling, specifically simple random sampling. The analysis method used was Partial Least Square (PLS). The study showed that communication training and internal frequency influenced job satisfaction. Communication training and the frequency of internal meetings influenced job satisfaction. Based on the results of the study, there was a partial influence of communication training and internal meeting frequency on job satisfaction, and this was mediated by internal communication. Based on the results of this study, it shows that mediation from internal communication plays an important role in strengthening the positive impact of job satisfaction on nurses at Sultan Iskandar Muda General Hospital, Nagan Raya